2014
DOI: 10.3144/expresspolymlett.2014.86
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of molecularly imprinted polypyrrole/titanium dioxide nanocomposites and its selective photocatalytic degradation of rhodamine B under visible light irradiation

Abstract: Abstract. Highly selective molecularly imprinted nanocomposites MIP RhB -PPy/TiO 2 were successfully prepared by surface molecular imprinting technique with rhodamine B (RhB) as template molecule. The prepared MIP RhB -PPy/TiO 2 coated with a thin imprinted layer could respond to visible light. The static and dynamic binding experiments revealed that MIP RhB -PPy/TiO 2 possessed strong affinity, high adsorption capacity and fast adsorption rate for RhB. The selectivity experiments indicated that MIP RhB -PPy/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…[268] In addition to their persistencea nd bioaccumulation, these molecules tend to move very long distances and are then deposited away from their emission sites;s uch speciesi nclude pesticides, hydrocarbons, dyes, and drugs. [273] Several studies report on the photodegradationo fd yes as model pollutants, such as methylene blue, [274] methyl orange, [275] rodamine B, [276][277][278] brilliant green, [279,280] phenol, [281,282] and acid red, [283,284] by TiO 2based photocatalyst under visible light. [273] Several studies report on the photodegradationo fd yes as model pollutants, such as methylene blue, [274] methyl orange, [275] rodamine B, [276][277][278] brilliant green, [279,280] phenol, [281,282] and acid red, [283,284] by TiO 2based photocatalyst under visible light.…”
Section: Organic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[268] In addition to their persistencea nd bioaccumulation, these molecules tend to move very long distances and are then deposited away from their emission sites;s uch speciesi nclude pesticides, hydrocarbons, dyes, and drugs. [273] Several studies report on the photodegradationo fd yes as model pollutants, such as methylene blue, [274] methyl orange, [275] rodamine B, [276][277][278] brilliant green, [279,280] phenol, [281,282] and acid red, [283,284] by TiO 2based photocatalyst under visible light. [273] Several studies report on the photodegradationo fd yes as model pollutants, such as methylene blue, [274] methyl orange, [275] rodamine B, [276][277][278] brilliant green, [279,280] phenol, [281,282] and acid red, [283,284] by TiO 2based photocatalyst under visible light.…”
Section: Organic Compoundsmentioning
confidence: 99%
“…[269][270][271][272] Removing organic contaminants by photocatalysis has been shown to be more efficient than conventional wastewater treatment such as filtration. [273] Several studies report on the photodegradationo fd yes as model pollutants, such as methylene blue, [274] methyl orange, [275] rodamine B, [276][277][278] brilliant green, [279,280] phenol, [281,282] and acid red, [283,284] by TiO 2based photocatalyst under visible light. Wand et al [285] outline the elaboration of carbon-sensitized and nitrogen-doped TiO 2 (C/N-TiO 2 )b yu sing the sol-gelm ethod.…”
Section: Organic Compoundsmentioning
confidence: 99%
“…RhB can cause the light transmittance of the water body to drop and destroy the ecological environment even at low concentrations. He et al [86] used RhB as the template molecule and successfully prepared MIPs RhB –PPy/TiO 2 (polyacrylamide/titania) by surface molecular imprinting using RhB as the template molecule. Static and dynamic binding experiments and selective experiments showed that MIPs RhB –PPy/TiO 2 had strong affinity and adsorption capacity, fast adsorption rate and good recognition selectivity to RhB.…”
Section: Application Of Tio2 and Their Composites Based Molecularlmentioning
confidence: 99%
“…Among the metal oxide NPs, titanium dioxide (TiO 2 ) NPs have been exploited as a potential material for numerous applications because of their unique properties, including high surface area and high catalytic efficiency [ 22 , 23 ]. These properties work to enhance the interaction between biomolecules and the surfaces of electrodes because they afford a greater accessibility of the target molecules to the sensing area [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%